Analyzing Learners’ Knowledge to Guess The Meaning of Vocabulary from Narrative Text - Nurlaela, Nurlaela; Melani, Boniesta Zulandha; Putera, Lalu Jaswadi; Saputra, Agus (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study investigates learners' knowledge to guess the meaning of vocabulary in narrative texts. The background emphasizes the significance of vocabulary in mastering English, especially for communication and comprehension. This study aims to determine students' knowledge in guessing the meaning of vocabulary in narrative texts. Students also have difficulty understanding the meaning of the text given because of their lack of vocabulary knowledge. The research employs a quantitative descriptive method, focusing on 8th-grade students at a junior high school. Data were collected using narrative texts and vocabulary lists in open-ended tests. Findings show that most students struggled to guess word meanings from context, with 74.01% classified as having no knowledge, 18.19% having full knowledge, and 6.17% partial knowledge. students cannot find the meaning of the vocabulary in the narrative text that has been provided. Most of them do not know the meaning of the context of the textThe study suggests using contextual learning strategies to improve vocabulary acquisition.